Pentad Analysis of Presidential Elections 2024 on Social Media - Moekahar, Fatmawati; Basista, Ronny; Syafhendry, Syafhendry; Taufiq, Ivan (P3M Politeknik Negeri Media Kreatif, 2024)
This article aims to analyze Ganjar Pranowo's posts on social media. Ganjar Pranowo is one of the presidential candidates who has great potential in the 2024 presidential election because he is one of the candidates from the winning party (incumbent) in the previous election. As a presidential candidate, Ganjar realizes the importance of social media in socializing himself and building a positive image as a presidential candidate. One social media platform that is well managed is Instagram. On his Instagram account, namely @ganjar_pranowo, Ganjar posts all his activities as part of political communication in an effort to attract the attention of the Indonesian people ahead of the election. The research method used is a qualitative method with pentad analysis consisting of 5 elements: act, scene, agent, agency and purpose). The research results found that Ganjar plays as the main actor and rhetorical communicator (act); applies election and social media (scene); roles as a political actor with a humanist and simple figure (agent); nationalist-religious (agency); and he attracts public attention, public sympathy and winning elections (purpose).